The Impact of the Announcement of Temporary Building Sites for Refugees on House Prices in Gothenburg - Josef Kjellander; Viktor Nilsson; Aico van Vuuren (Institute of Labor Economics (IZA), 2018)
We evaluate the price development of apartments in neighborhoods surrounding temporary housing for refugees using the unpredicted announcement of three building sites, targeting refugees, in Gothenburg. More in particular, we look at the price development in the year after the announcement. We use a causal outcome model that takes account of time and postal-code fixed effects and we define an area to be affected by the announcement based on walking distance. We find support for a small and significant price effect. In addition, we find that the price effect of the neighborhood depends on the income level of the neighborhood. We interpret this as evidence for the fact that not having to live close to refugees can be seen as a luxury good.
Keywords: O15; O18; R31; 330; house prices; migration